Transforming Physical Browsing in Library using IoT - Supe, Aarti; Waghchaure, Yogesh K; Shede, Raj R; Sutar, Rohit R (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things characterized as interconnection of exceptionally identifiable inserted processing gadgets inside the current framework. Sooner rather than later the world will be overlaid with correspondence of installed gadgets making a "Savvy World". The world is splashed in the web and now the Internet of Things is additionally picking up a considerable measure of consideration. However, the utilization of the web innovation in library administration is at its earliest stages. In spite of the fact that standardized tag or BLE-BEACONS based library administration framework has raised effectively in the current past, it has its own constraints. The proposed framework depends on the BLE-BEACONS innovation where BLE-BEACONS are inserted on the books shelf and the client advanced mobile phone can connect to it through its Bluetooth device for simple, productive and efficient physical browsing in library. This framework utilizes client's own advanced mobile phone to see the whole book data available on multiple BLE-BEACONS device in its range. One of the significant objectives of this IoT based "Brilliant Library System" is rearranging the client's undertaking of hunting down the books and issuing books.